XSP10 and SlSAMT, Fusarium wilt disease responsive genes of tomato (Solanum lycopersicum L.) express tissue specifically and interact with each other at cytoplasm in vivo - Debbarma, Johni; Saikia, Banashree; Singha, Dhanawantari L.; Maharana, Jitendra; Velmuruagan, Natarajan; Dekaboruah, Hariprasanna; Arunkumar, Kallare P.; Chikkaputtaiah, Channakeshavaiah (Physiology and molecular biology of plants, 2021)
Fusarium wilt caused by Fusarium oxysporum f. sp. lycopersici ( Fol ) is a major fungal disease of tomato ( Solanum lycopersicum L.). Xylem sap protein 10 ( XSP10) and Salicylic acid methyl transferase ( SlSAMT) have been identified as putative negative regulatory genes associated with Fusarium wilt of tomato. Despite their importance as potential genes for developing Fusarium wilt disease tolerance, very little knowledge is available about their expression, cell biology, and functional genomics. Semi-quantitative and quantitative real-time PCR expression analysis of XSP10 and SlSAMT, in this study, revealed higher expression in root and flower tissue respectively in different tomato cultivars viz. Micro-Tom (MT), Arka Vikas (AV), and Arka Abhed (AA). Therefore, the highly up-regulated expression of XSP10 and SlSAMT in biotic stress susceptible tomato cultivar (AV) than a multiple disease resistant cultivar (AA) suggested the disease susceptibility nature of these genes for Fusarium wilt. Sub-cellular localization analysis through the expression of gateway cloning constructs in tomato protoplasts and seedlings showed the predominant localization of XSP10 in the nucleus and SlSAMT at the cytoplasm. A strong in vivo protein–protein interaction of XSP10 with SlSAMT at cytoplasm from bi-molecular fluorescent complementation study suggested that these two proteins function together in regulating responses to Fusarium wilt tolerance in tomato.